Antioxidant and anti-matrix metalloproteinases activities of dried longan (Euphoria longana) seed extract - Atita Panyathep (2018)
Longan, a major fruit crop in Thailand, is a rich source of antioxidant polyphenic compounds, mostly gallic acid and ellagic acid. Dried longan seeds contain large amounts of antioxidant polyphenols. In this study, three fractions of dried longan seed extract were collected by Sephadex LH-20 column chromatography to determine the major compounds in each, and the amounts of gallic acid and ellagic acid were quantified. The first fraction was determined to be the major source of gallic acid, while ellagic acid was mainly found in fraction 3. Antioxidant activities were measured using total phenolic content, total flavonoid content, 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity, and metal chelating activity. Fraction 1 had the highest antioxidant activity. In addition, the effect of each fraction on matrix metalloproteinases (MMPs) activity was analysed using a fluorometric assay. Interestingly, fraction 3 had the greatest MMPs inhibitory effect. Notably, dried longan seeds have been established not only as major sources of antioxidants, but also as potent MMPs inhibitors. Since these properties are associated with anti-cancer effects, dried longan seeds could be a novel natural source for compounds used in chemoprevention and chemotherapy.